Exploring the Relationship Among Free-Time Management, Leisure Boredom, and Internet Addiction in Undergraduates in Taiwan. Issue 5 (October 2019) - Wang, Wei-Ching
Internet addiction has become a significant concern with a variety of negative outcomes among the younger generation in today's modern society and has been investigated and discussed in many studies. Of all the influencing factors, boredom has been proven to be a common trigger for intensive internet use and can result in particularly problematic internet use behavior. A number of studies have indicated the importance of time use as a treatment. Thus, using free time well might serve as a solution to reduce leisure boredom and internet addiction. The current study aims to test a structural model with a sample of university students to investigate the relationships among free-time management, leisure boredom, and internet addiction. The sample consisted of 475 undergraduate students. Data were collected through questionnaires distributed between March 1 and April 30, 2016. Totally, 446 valid questionnaires were received. The structural model was examined after the competent measurement model was processed. Results from the structural model supported that free-time management decreases boredom during leisure time, and boredom during leisure time enhances internet addiction. Furthermore, leisure boredom was revealed to play a role as a distinct mediator between free-time management and internet addiction. Finally, managerial applications and recommendations for future research are suggested based on the research results.